Escherichia coli displays a conserved membrane proteomic response to a range of alcohols - Oishi Sen; Jamie Hinks; Qifeng Lin; Qingsong Lin; Staffan Kjelleberg; Scott A. Rice; Thomas Seviour (Biotechnology for Biofuels and Bioproducts, 2023)
Abstract Background Alcohol is a good and environment-friendly fuel that can be microbially produced, capable of eliminating many of the limitations of the present-day fossil fuels. However, the inherent toxic nature of alcohols to the microbial cells leads to end-product inhibition that limits large-scale alcohol production by fermentation. Fundamental knowledge about the stress responses of microorganisms to alcohols would greatly facilitate to improve the microbial alcohol tolerance. The current study elucidates and compares the changes in the membrane proteome of Escherichia coli in response to a range of alcohols. Results Although alcohol toxicity increased exponentially with alcohol chain length (2–6 carbon), similar stress responses were observed in the inner and outer membrane proteome of E. coli in the presence of 2-, 4- and 6-carbon alcohols at the MIC50. This pertains to: (1) increased levels of inner membrane transporters for uptake of energy-producing metabolites, (2) reduced levels of non-essential proteins, associated with anaerobic, carbon starvation and osmotic stress, for energy conservation, (3) increased levels of murein degrading enzymes (MltA, EmtA, MliC and DigH) promoting cell elongation and 4) reduced levels of most outer membrane β-barrel proteins (LptD, FadL, LamB, TolC and BamA). Major outer membrane β-barrel protein OmpC, which is known to contribute to ethanol tolerance and membrane integrity, was notably reduced by alcohol stress. While LPS is important for OmpC trimerisation, LPS release by EDTA did not lower OmpC levels. This suggests that LPS release, which is reported under alcohol stress, does not contribute to the reduced levels of OmpC in the presence of alcohol. Conclusions Since alcohol primarily targets the integrity of the membrane, maintenance of outer membrane OmpC levels in the presence of alcohol might help in the survival of E. coli to higher alcohol concentrations. The study provides important information about the membrane protein responses of E. coli to a range of alcohols, which can be used to develop targeted strategies for increased microbial alcohol tolerance and hence bioalcohol production.